Facebook versus television: Advertising value perceptions among females - Dix, S.; Ferguson, Graham; Logan, K.; Bright, L.; Gangadharbatla, H. (Emerald Group Publishing Limited, 2012)
The purpose of this paper is to compare female students' perceptions of the value of advertising on social network sites (SNSs) to their perceptions of the value of television advertising. An online questionnaire was fielded among students from three major universities in the USA, as well as SNSs (Facebook, LinkedIn, and Twitter). The final sample (n=259) was comprised of female students who had used social media and television during the past month. The authors developed two structural equation models using Amos 18 statistical software. The analysis indicated that Ducoffe's Ad Value model does not provide a good fit for assessing advertising value in social media or television. While Irritation was a factor in assessing Attitude toward advertising, the respondents assessed ad value on the basis of Entertainment (higher for social media) and Informativeness (higher for television). In examining the relative importance of each component of Ducoffe's model, it is clear that Entertainment and Informativeness play key roles in assessing advertising value for both traditional (television) and non-traditional media (SNSs). While Irritation did not play a significant role in value assessment, it was found to directly impact attitude towards advertising, a critical juncture in the consumer purchase cycle. If practitioners seek to interact via SNSs with young female consumers they should focus on providing entertaining content in a format that makes brand engagement seamless while not impeding goals. This initial investigation provides the impetus for future research about consumers' perceptions of advertising value across all SNSs, in comparison to their traditional counterparts.